Processo de implementação do PBQP-H: o caso dos municípios paranaenses - Rezende, Joversi Luiz de (2013)
This research is focused on the construction industry, which is seeking to respond to market demands and ensure acting perspective in a context increasingly demanding and competitive, and thus resorts to the implementation of Quality Management Systems. Thus, this study aims to verify how was the process of implementation of the Brazilian Program of Quality and Productivity Habitat (PBQP-H) in companies of Construction, located in Maringa, Parana State. Methodologically, we chose an approach of case study research strategy with exploratory and descriptive, with the level of analysis and the organizational units of analysis composed of individuals corporate executives in the study. Results indicated that the implementation of PBQP-H allows to obtain several benefits for companies such as: improved communication work / office, waste reduction, qualification of labor, among others, not restricted to the achievement of objectives punctual. Albeit indirectly, it is clear that there is greater awareness in optimizing the traditional construction process, after the implementation of the program.